EVALUATING NEUROMARKETING TECHNIQUE ON CONSUMER SATISFACTION USING EEG IMAGING - Mahamad, N.A.; Amin, M.K.M.; Mikami, O. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
This article presents an evaluation of consumer satisfaction using the EEG brain imaging technique. Involvement of brain science into marketing research has sparked great interest recently since traditional marketing solely dependent on questionnaires. Consumers are normally less cooperative with marketers when they made an unexplained decision by answering the questionnaires. In response to this problem, the EEG imaging technique could be used to identify the consumer response by analyzing their brain activities. A low-cost Emotiv EPOC EEG Neuroheadset was used in this experiment. Theta (ϑ) 4-8 Hz, Alpha (α) 8 to 12 Hz and Beta (β) 12-25 Hz waves are the basis for determining the brain activation. Popular shoes product advertisement on price reduction were displayed on the computer screen to observe the subject’s responses. The topographic maps result of the brain showed that the frontal lobe and the right part of the brain activated the most which indicates the contentment or satisfaction behaviour. Further analysis on the power spectral density showed that higher synchronization of Theta (ϑ), Alpha (α) and Beta (β) bands were more apparent in the right frontal lobe which thus confirmed a significant correlation of marketing decisions with the brain activities.